The Impact of Competence on Digital Leadership Toward Curriculum Management and Teaching Performance of Islamic Lesson of SMP Teachers in Bogor - Gunarti Sukriyatun; Budi Handrianto; Muh. Arbiyansyah Nur (International Journal of Asian Business and Management, 2023)
The purpose of the study was to investigate the impact of Digital Leadership Competencies on Curriculum Management and Islamic Learning Performance. The research method used is qualitative research with a case study approach. Data collection techniques in the form of interviews with participants, field observations, documentation studies. The findings consist of two topics of discussion. First, that there has been a curriculum innovation that is tailored to the needs of teachers and students during the Covid 19 pandemic. The learning syllabus has become simpler, learning hours are simpler and achievement targets are lower than they should be in face-to-face meetings. Second, the leadership carried out by digital-based principals has not had an optimal impact in helping teachers improve their performance. Principals have not routinely conducted virtual assessments of teacher performance. As a result, teachers find it difficult to run online learning because of some perceived deficiencies to be a challenge for teachers. It is a special concern that there is still a syllabus whose basic competency target is very high, in online learning conditions it will be difficult to achieve the expected basic competency target